A comparison of job stress models: associations with employee well-Being, absenteeism, presenteeism, and resulting costs - Schmidt, Burkhard; Herr, Raphael (Journal of occupational and environmental medicine, 2019)
Objective: This study investigates the associations between Effort-Reward-Imbalance (ERI), Overcommitment (OC), Job-Demand-Control (JDC), and Organizational Injustice (OIJ) with employee well-being, absenteeism, and presenteeism, as well as the costs incurred. - Methods: Cross-sectional data from 1440 German pharmaceutical company employees assessing job stress, employee well-being, absenteeism, and presenteeism were used. Linear regression and interval regression analyses assessed separate and independent associations and sample-specific costs were estimated. - Results: All four stressors were related to employee well-being, presenteeism, and absenteeism when analyzed separately. OIJ showed the strongest independent association with absenteeism (coef. = 0.89; P < 0.01), whereas OC was most strongly independently associated with lower well-being (coef. = −0.44; P < 0.01) and higher presenteeism (coef. = 0.28; P < 0.01). Absenteeism costs per employee/year were higher than presenteeism costs. - Conclusions: Occupational health interventions reducing job stress will have strong potential for productivity raise and lower costs.
Gesehen am 13.01.2020